Effects of Maltodextrin on Characteristics of Calamansi Orange Peel (Citrofortunella microcarpa) as A Green Tea Flavor: Effects of Maltodextrin on Characteristics of Calamansi Orange Peel (Citrofortunella microcarpa) as A Green Tea Flavor - Silsia, Devi; Sidebang, Bosman; Silalahi, Ayu Sagita Putri (Agroindustrial Technology Journal, 2025)
Calamansi orange peel contains bioactive compounds and essential oils but has not been utilized and is only thrown away as waste. This research aims to determine the effect of adding maltodextrin in the drying process on the characteristics of calamansi orange peel and to obtain panelist acceptance of its use as a green tea flavor. The study used a Completely Randomized Design (CRD) with 1 factor, namely maltodextrin concentration (6%, 8%, 10%). Drying was carried out for 7 hours using an oven at 60 â°C. The organoleptic test was carried out by brewing 3 g of a mixture of green tea with calamansi peel powder in a ratio of 1:2 in 220 ml of hot water t a temperature of 85 â°C for 5 minutes. The results of the research showed that the calamansi peel powder produced had a water content of 1.41-3.41%, vitamin C of 58.67-108.53 (mg/100g), and a volatile reducing substance (VRS) content of 6.5 -12 meq. The panelists' highest level of preference for calamansi powder as a green tea flavor was obtained in the treatment with the addition of 10% maltodextrin in the range of liking to very liking